THE IMPORTANCE OF ENGLISH IN VOCATIONAL EDUCATION - Obidova Gulshoda Khidirovna; Khaydarova Asal Fakhriddin qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION This article examines the importance of teaching English in the  vocational  education  system,  its  close  relationship  with  modern  labor  market requirements, and its role in developing professional competencies. Particular attention is paid to teaching English in vocationally oriented technical and vocational education institutions. In addition, the theoretical foundations and practical effectiveness of ESP (English for Specific Purposes) and CLIL (Content and Language Integrated Learning) approaches  are  analyzed  as  effective  methods  for  teaching  English  in  vocational education.